MUC563 : Orchestration techniques / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2023)
In this course, students will analyze orchestral works of different historical periods, genres and styles. They will learn advanced orchestral scoring techniques and will develop an understanding of how instrumental colour interacts with harmonic colour in an orchestral context. Students will also transcribe pieces for piano and/or chamber ensemble to standard symphony orchestra. scoring techniques and will develop an understanding of how instrumental colour interacts with harmonic colour in an orchestral context. Students will also transcribe pieces for piano and/or chamber ensemble to standard symphony orchestra.